Exploring the Role of Environment Service Quality in Enhancing Customer Satisfaction During Umrah in Malaysia - Abdul Talib, Khadijah; Harun, Amran; Abu Seman, Noor Aslinda (JBS Nexus, 2025)
The Umrah industry in Malaysia faces numerous challenges, particularly fraud, which leads to high customer dissatisfaction with the services offered by Umrah operators. Environmental service quality difficulties in Umrah refer to the challenges of cleanliness, sustainability, and infrastructure that impact pilgrims’ experiences and contentment. To address this, the study examines the relationship between environmental service quality (focused on airline service, hotel service, transportation service, and ambient) and customer satisfaction during the Umrah. This study employed a quantitative, cross-sectional approach, with 219 Umrah pilgrims aged 28 to 58 being the most significant sample of travellers. Respondents are chosen using convenience sampling. Data is gathered via online questionnaires and direct participation at airports like KLIA and KLIA 2. The research objective was achieved via descriptive analysis and multiple regression. This study also helps to understand customer satisfaction and demands, which is essentially the degree to which customers are satisfied with services, particularly those provided by airlines, hotels, transportation, and the environment, which can contribute to people’s satisfaction while performing Umrah.